Educator of Sustainable Development as the Response to the Need of Sustainable Society Education - Gajuś-Lankamer, Ewa; Wójcik, Anna Maria (Problemy Ekorozwoju, 2011)
The article presents the selected issues in education for sustainable development. It consists of the characteristics of this education. The main emphasis has been placed on the presentation of an original concept of educator for sustainable development educator. A description of such educator was given. The education model and the effects of its use in the practice of higher education were also shown.